Performance improvement project in the sterile processing department at a university hospital in Egypt - Redesign to centralize the process - El-sokkary, Rehab Hosny; Ramadan, Raghdaa A; Soliman, Manar H (International Journal of Infection Control, 2015)
Reprocessing of medical instruments is a complex process requiring several steps. In the last few years, many reports were delivered to our infection control unit about defects in the sterilization service. This study aims to describe improvements in the performance of the Sterile Processing Department (SPD), thus improving safety for patients and healthcare professionals. The FOCUS-PDCA strategy and root cause analysis were used to define the problem, investigate the underlying causes and develop a quality improvement plan. Defects in the service provided were detected, including inadequate procedures and training, breaches in reprocessing, and suboptimal workplace ergonomics and design. We developed an institutional policy and standard operating procedures for the SPD, implemented a training program for SPD staff, and improved the workplace layout to improve separation of clean and soiled equipment.